Selective Thermotolerant Lactic Acid Bacteria Isolated From Fermented Juice of Epiphytic Lactic Acid Bacteria and Their Effects on Fermentation Quality of Stylo Silages - Pitiwittayakul, Nittaya; Bureenok, Smerjai; Schonewille, Jan Thomas (Frontiers in Microbiology, 2021)
The aim of the present study was to isolate and identify lactic acid bacteria (LAB) from fermented juice of tropical crops as Napier grass, Ruzi grass, Purple guinea grass, Stylo legume and Leucaena and their application to improve the quality of tropical crop silage. Fifteen strains of LAB were isolated. The LAB strains were Gram-positive and catalase-negative bacteria, and could be divided into 3 groups, i.e. Pediococcus pentosaceus, Lactiplantibacillus (para)plantarum and Limosilactobacillus fermentum according to biochemical API 50CH test. Based on the analysis of 16S rRNA sequence, the strains isolated in group Lactiplantibacillus (para)plantarum were distinguished. Two isolates (N3 and G4) were identified as Lactiplantibacillus plantarum. Three isolates (St1, St2 and St3) were identified as Lactiplantibacillus paraplantarum. In addition, the identification of other isolates was confirmed in group P. pentosaceus (R1, R4, R5, R8, R11 and L1) and group L. fermentum (N4, G6, G7 and N4). All selected strains were able to grow at 50 °C. All LAB strains showed antimicrobial activity against Escherichia coli ATCC 25922, Shigella sonnei ATCC 25931, Pseudomonas aeruginosa ATCC 27853 and Bacillus cereus ATCC 11778. Four selected LAB strains (St1, St3, N4 and R4) were tested for their capacity to successfully ensile Stylo legume (Stylosanthes guianensis CIAT184). Stylo silages treated with LAB were well-preserved, the NH3-N and butyric acid contents were lower, and the lactic acid content was higher than those in the control (P<0.05). Acetic acid content was highest in R4-treated silage among the treatments (P<0.05). The crude protein content of St1-silage was significantly (P<0.05) higher than the others. Inoculation of thermotolerant LAB selected from FJLB was found to be highly instrumental to obtain well preserved silage from Stylo legume.